Ações educativas no pré-natal: uma análise crítica e reflexiva sobre a consulta de enfermagem como um espaço para educação em saúde - Rios, Claudia Teresa Frias (2003)
In the search of new ways that best thought about the nursing consultation as a space for the education in health in the prenatal, took place a criticai and reflexive study through a qualitative evaluation where the participation of the involved subjects went a preponderant factor. For so much it rushed hand of a new paradigm as methodological referential, the evaluation emancipation, that orientated the stages of this research: description of the reality; critic of the reality and collective creation. Besides the observation and of the interview, the technique of the focal group was the most important for the collection of data and for the five nurses' participation that act at the clinic of the Academical Hospital, chosen place for the research. Front to the found results the educational action accomplished by the nurse during the consultation of the prenatal is characterized as an action routine, little share, with informative predominance in spite of the existence of the objective and good purpose of educating, where subjects related to the assistance model, structural and organizational of the Institution they emerged as obstacles for the accomplishment of the education in health as tendency liberty, critical-social and changer. For middle of that methodological construction and with base in the critic of the reality, other relevant point of this research was the collective creation, where you idealize generating of changes they were pointed for the participants. Those generating ideas appear for the reorientation of the nursing Service in the attention to the pregnant woman of the Academical Hospital; the creation of an appropriate physical atmosphere for the Service of the nursing consultation and the pregnant woman's participation in groups.